2023
DOI: 10.3389/fimmu.2023.1162633
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental octanoate on hepatic lipid metabolism, serum biochemical indexes, antioxidant capacity and inflammation-related genes expression of large yellow croaker (Larimichthys crocea) fed with high soybean oil diet

Abstract: Dietary high soybean oil (SO) levels might cause hepatic lipid deposition, induce oxidative stress and inflammatory response in aquatic animals, while octanoate (OCT) is beneficial to metabolism and health in mammals. However, the effect of OCT has been studied rarely in aquatic animals. In this study, a 10-week feeding trial was conducted to investigate the effect of supplemental OCT on hepatic lipid metabolism, serum biochemical indexes, antioxidant capacity and inflammatory response of large yellow croaker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…Previous studies have found that the antioxidant capacities were reduced in large yellow croaker fed SO diets when compared with FO diets [ 82 ]. In our study, there were lower expression levels of GPX3 in the muscle of the SO groups when compared with FO and RO, which is similar to previous results in large yellow croaker [ 84 ], indicating that SO could reduce the antioxidant capacity in largemouth bass. Many studies have demonstrated that transcriptional variations in these antioxidant enzymes are mainly modulated by the Nrf2 signaling pathway in humans and animals [ 82 , 85 , 86 ].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have found that the antioxidant capacities were reduced in large yellow croaker fed SO diets when compared with FO diets [ 82 ]. In our study, there were lower expression levels of GPX3 in the muscle of the SO groups when compared with FO and RO, which is similar to previous results in large yellow croaker [ 84 ], indicating that SO could reduce the antioxidant capacity in largemouth bass. Many studies have demonstrated that transcriptional variations in these antioxidant enzymes are mainly modulated by the Nrf2 signaling pathway in humans and animals [ 82 , 85 , 86 ].…”
Section: Discussionsupporting
confidence: 91%